Keterkaitan parameter nilai pH, C-organik, N-Total, C/N dan alofan pada beberapa Andisols di Jawa Barat - Rina Devnita; Mahfud Arifin; Ridha Hudaya; Ade Setiawan; Apong Sandrawati (Soilrens, 2017)
The correlation of chemical parameters and soil mineralogy one to another in Andisols were interesting to be studied, to increase the understanding of soil reactions, nutrient availability and soil mineral content. Andisols from three locations and derived from three different volcanic eruptions namely G. Tangkuban Parahu, G. Patuha and G. Tilu, with andesite, andesite-basalt and basalt parent materials respectively, were examined the correlation of several soil parameters. The values of pH, organic carbon, total nitrogen, C/N and allophane content were obtained from the soil analysis of every horizon of the soil profiles at each site. Correlation analyses were used to see the relationship of the parameters. The results showed a negative correlation between pH and organic carbon (r = -590 *). The soil pH values were positively correlated with the amount of allophane (r = 0.687 *). The pH values were correlated positively with imogolite content (r = 0.356 *). The pH values were negatively correlated with organic carbon (r = -0.590 *). The organic carbon content was negatively correlated with depth (r = - 0.582 *). The organic carbon content was negatively correlated with allophane (r = 0.707 *). Total nitrogen values were negatively correlated with increasing depth (r = -0.531 *).Keywords: Mt. Tangkuban Parahu, Mt. Patuha, Mt. Tilu, andesit, andesit-basalan, alophane